Low-carbon steel oxide scale reduction annealing process and hot galvanizing process
The iron oxide sheet is destroyed by water/abrasive sandblasting treatment and high-temperature heating, and the iron oxide sheet is completely reduced with reducing gas, which solves the problem of the iron oxide sheet hindering the quality of the coating, and achieves a galvanized layer with high adhesion and uniformity, and is environmentally friendly in the process.
Patent Information
- Application Number
- CN202411821189.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
The iron oxide sheet formed on the surface of low carbon steel during hot rolling hinders the sufficient reaction between the zinc liquid and the steel surface, affecting the quality and performance of the plating. Traditional pretreatment methods such as pickling have problems such as environmental pollution and unenvironmental protection.
Water/abrasive sandblasting is used to combine high-temperature heating to destroy the integrity of the iron oxide sheet, and then reduce and annealery under a reducing gas atmosphere to form thorough metal iron and a small amount of ferrous oxide, improving the adhesion between the zinc layer and the substrate.
Through thorough iron oxide reduction, the adhesion and uniformity of the galvanized layer can be improved, the corrosion resistance of the plating layer is enhanced, environmental pollution is reduced, and the process flow is more environmentally friendly.
Smart Images

Figure BDA0005183144520000101 
Figure BDA0005183144520000102
Abstract
Description
Technical Field
[0001] The present application relates to the field of metal processing, and more specifically, to a low-carbon steel scale reduction annealing process and a hot-dip galvanizing process. Background Art
[0002] Modern industry has higher and higher requirements for materials. In addition to mechanical properties such as strength and toughness, corrosion resistance and appearance have also become increasingly important properties. Among them, low-carbon steel, as a common material, has been widely used in many fields. With the rapid development of the steel industry and the wide application of steel materials in various fields, higher and higher requirements are put forward for the anti-corrosion performance and surface quality of steel. The traditional hot-dip galvanizing process has excellent anti-corrosion performance and is widely used.
[0003] However, during the hot rolling process, a layer of iron oxide scale, mainly composed of ferric oxide, ferric oxide and ferrous oxide, will be produced on the surface of low carbon steel. The presence of this iron oxide scale will affect the subsequent processing and surface quality of the steel, especially in the hot-dip galvanizing process, which will hinder the full infiltration and reaction of the zinc liquid with the steel surface, thereby affecting the quality and performance of the coating. Therefore, before hot-dip galvanizing, the steel surface needs to be properly pretreated to remove the iron oxide scale and improve its surface properties.
[0004] In the traditional hot-dip galvanizing process of hot-rolled strip steel, pickling, shot blasting and other methods are often used to remove the iron oxide. Pickling generates waste acid and waste liquid, pollutes the environment, is not energy-saving and environmentally friendly, and causes the entire hot-dip galvanizing production process to be relatively long. In order to solve the drawbacks of the traditional process, some scholars have proposed using reducing gases such as hydrogen to react with oxides in the iron sheet, using this new process to replace the traditional process. However, the traditional reduction annealing process is difficult to completely reduce the iron oxide, which affects the quality of subsequent hot-dip galvanizing, resulting in poor adhesion of the zinc layer, and affecting the quality and performance of the subsequent coating. Summary of the invention
[0005] In order to achieve effective reduction of iron oxide scale, ensure good adhesion between the zinc layer and the substrate, and improve the quality of the coating, the present application provides a low-carbon steel iron oxide scale reduction annealing process and a hot-dip galvanizing process.
[0006] In a first aspect, the present application provides a low-carbon steel oxide scale reduction annealing process, which adopts the following technical solution: a low-carbon steel oxide scale reduction annealing process, comprising the following steps: S1. Pretreatment: The hot-rolled steel strip substrate is first treated with water / abrasive sandblasting and then washed with water, and then heated to 650-700°C at a heating rate of 50-60°C / s. After the heat preservation treatment, the substrate is taken out and immediately placed in a salt solution to obtain a pretreated substrate; S2. Reduction annealing: The prepared pretreated substrate is subjected to reduction annealing in a reducing gas atmosphere at a reduction temperature of 700-860°C.
[0007] By adopting the above technical scheme, the outermost layer of the reduced iron scale is ferric oxide with a crystalline structure, the middle layer is dense, non-porous and crack-free magnetic ferroferric oxide with a glass-like fracture, and the inner layer is loose and porous ferrous oxide. In the present application, the substrate is first subjected to water / abrasive sandblasting treatment and then subjected to high-temperature heating, so that microcracks are formed on the iron scale under the above-mentioned mechanical action and thermal processing, thereby destroying the integrity of the iron scale layer, and then reduction annealing treatment is carried out under reducing gas to provide a channel for the reducing gas to diffuse inward, thereby accelerating the reduction process, especially the dense structure of the outer layer and the middle layer forms a channel, so that the reduction of the iron scale is more thorough.
[0008] Compared with the current reduction annealing treatment directly performed on the substrate, after the outer layer is reduced to metallic iron or ferrous oxide, ferroferric oxide still remains inside. Since ferroferric oxide is different from metallic iron, it affects the quality of the coating during the hot-dip galvanizing process. In this application, the integrity of the iron oxide scale is destroyed and its reduction is more thorough to form metallic iron and a small amount of ferrous oxide in the inner layer. Metallic iron has good wettability and reactivity, and is easy to combine with zinc liquid to form a tight galvanized layer; reduction to metallic iron can significantly improve the adhesion and uniformity of the galvanized layer, thereby improving the overall quality of hot-dip galvanizing. The presence of ferrous oxide does not have a negative impact on the formation of the galvanized layer. On the contrary, these oxides have good wettability and reactivity, which helps the formation of the galvanized layer. In this way, the good adhesion between the galvanized layer and the substrate is improved through the reduction annealing process in this application, and the quality of hot-dip galvanizing is improved.
[0009] Optionally, in step S1, the specific operation of water / abrasive sandblasting is: Water and quartz sand are mixed in a mass ratio of 1:(0.1-0.2) to obtain a mortar, which is then sprayed onto a hot-rolled steel strip substrate at a spray distance of 50-80 mm, a spray pressure of 1.5-3.5 MPa, and a spray flow rate of 0.1-0.3 kg / min.
[0010] By adopting the above technical solution and the above sandblasting parameters, it is possible to ensure that the integrity of the oxidized iron scale of the hot-rolled strip substrate is destroyed to form gaps that are conducive to the diffusion of reducing gases, while not causing damage to the substrate, and ultimately the performance of the hot-dip galvanized stainless steel is better.
[0011] Optionally, the particle size of the quartz sand is 40-80 mesh, the sandblasting angle is controlled to be 45-60 degrees, and the sandblasting time is 3-5 minutes.
[0012] By adopting the above technical solution, the control of the sandblasting angle is more conducive to the stress on the middle layer and outer layer of the substrate iron oxide scale, and combined with the subsequent thermal stress treatment, the integrity of the iron oxide scale is destroyed, the reduction degree of the iron oxide scale is improved, and the quality of hot-dip galvanizing is improved.
[0013] Optionally, the salt solution in step S1 is a sodium chloride salt solution with a mass concentration of 35-45%, and its temperature is controlled at 3-8°C.
[0014] By adopting the above technical scheme, the substrate treated with water / abrasive sandblasting is treated at high temperature, and the substrate is washed with water and then treated at high temperature. The treatment under high temperature and water environment conditions and then quickly placed in a sodium chloride salt solution is helpful for the cracking of the iron oxide scale. Moreover, the high temperature treatment is followed by a rapid treatment in a low temperature salt solution, and the integrity of the iron oxide scale is destroyed through thermal stress changes, which is more conducive to the circulation and reduction effect of the reducing gas in the subsequent reduction annealing process, and the reduction of the iron oxide scale is more thorough.
[0015] Optionally, in step S2, the substrate is first treated in a hydrogen atmosphere at 700-780°C for 2-3 minutes, then 85-95% hydrogen and the remainder carbon dioxide are introduced, and carbon powder is sprayed onto the substrate at the same time. After treating for 2-3 minutes, hydrogen is continued to be introduced, and the temperature is raised to 780-860°C so that the gas pressure is reduced to 0.1-0.2MPa.
[0016] By adopting the above technical scheme, in the present application, when the reduction annealing process is processed, first reduction is carried out in a hydrogen atmosphere to reduce ferric oxide and ferroferric oxide to iron or ferrous oxide, and then a small amount of carbon dioxide is used to provide an oxygen source, and carbon powder is sprayed on the substrate at the same time, so that the carbon powder can exert its strong reducing property at high temperature and directly reduce the metal oxide, and a small amount of carbon dioxide is introduced to make the participating carbon react with carbon dioxide to generate carbon monoxide, so that the gas in the final reduction chamber is a mixed atmosphere of hydrogen and carbon monoxide. It can be seen from the Ellingham diagram that when there is enough carbon monoxide in the atmosphere, divalent iron is the most stable, and when hydrogen is present, divalent iron can also be converted into elemental iron. Therefore, compared with the traditional method of only using a reducing atmosphere for reduction annealing, the reduction is usually not thorough. In the present application, carbon element is introduced, and the regulation of the reducing gas is coordinated, and the reduction of the iron oxide scale is finally more thorough, which is more conducive to the subsequent hot-dip galvanizing process.
[0017] Optionally, the amount of carbon powder added in step S2 is 0.05-0.15wt% of the hot-rolled steel substrate.
[0018] By adopting the above technical solution, a small amount of carbon powder can be added to play a strong reducing role to directly reduce the metal oxide to a single substance, and a small amount of residual carbon forms a carbon monoxide atmosphere with carbon dioxide, thereby regulating the final carbon monoxide and hydrogen atmosphere concentrations, which can more thoroughly reduce the iron oxide.
[0019] Optionally, in step S2, the pretreated substrate is reduced in a reducing gas atmosphere, cooled to 500-560° C. at a cooling rate of 10-20° C. / s, and then cooled to 380-420° C. at a cooling rate of 30-40° C. / s.
[0020] In a second aspect, the present application provides a low carbon steel hot dip galvanizing process, which adopts the following technical solution: A low carbon steel hot dip galvanizing process comprises the following steps: 1) performing iron oxide reduction annealing treatment on the hot-rolled steel strip substrate according to the low-carbon steel iron oxide reduction annealing process; 2) The hot-rolled steel strip after the reduction annealing treatment of the iron oxide scale is hot-dip galvanized in zinc liquid to form a galvanized layer on the surface of the hot-rolled steel strip to obtain a hot-dip galvanized sheet.
[0021] By adopting the above technical scheme, the oxide layer is reduced to the original color of the metal after the reduction annealing treatment of the oxide scale of the hot-rolled strip substrate by the method provided in this application, thereby improving the adhesion between the zinc layer and the substrate, and the anti-corrosion performance of the galvanized sheet is greatly improved. In addition, acid washing is not used, which reduces environmental pollution and is more environmentally friendly.
[0022] Optionally, in step 2), the zinc solution comprises 0.15-0.3 wt% of aluminum, 0.05-0.08 wt% of magnesium and the balance of zinc.
[0023] By adopting the above technical scheme, a small amount of aluminum and magnesium are added to the zinc liquid to significantly improve the adhesion between the coating and the substrate. The aluminum element first reacts with the low-carbon steel substrate to form an iron-aluminum alloy to form an iron-aluminum compound intermediate layer that is tightly attached to the substrate, forming a transition layer between the zinc-plated layer and the substrate, providing strong adhesion for the zinc layer and enhancing the adhesion between the coating and the substrate. The addition of magnesium can inhibit the transitional growth of grains in the zinc layer, making the grains small and uniform, improving the density and uniformity of the coating, and enhancing the bonding between the coating and the substrate.
[0024] Optionally, the hot-rolled steel strip after the scale reduction annealing treatment in step S2 is first immersed and dried in a plating solution before hot-dip galvanizing in a zinc solution, wherein the plating solution contains 5-7wt% of ammonium chloride, 1-2wt% of acidic amino acid, 0.3-0.5wt% of 1-carboxymethyl-3-methylimidazole tetrafluoroborate, 10-15wt% of zinc chloride and the remainder of water.
[0025] By adopting the above technical scheme, the hot-dip galvanizing solution in the present application includes ammonium chloride and zinc chloride. The addition of ammonium chloride can decompose to produce hydroxy acid and hydroxide, which can decompose and remove the residual iron salt and unremoved iron oxide on the surface of the substrate, and can also reduce the surface tension of the zinc liquid, promote the rapid wetting and reaction between the body and the liquid zinc, and is conducive to the formation of a Zn-Fe alloy phase layer. Finally, the zinc plating solution in the present application forms a zinc ammonium complex salt to form a zinc ammonium chloride salt film on the stainless steel strip substrate after reduction annealing, which protects the steel from being oxidized again before entering the zinc liquid, and can also reduce the generation of zinc slag.
[0026] More importantly, the present application adds acidic amino acids and 1-carboxymethyl-3-methylimidazole tetrafluoroborate on the basis of zinc chloride and ammonium chloride. The amino group and carboxyl group in the molecular structure of the acidic amino acid react with the steel surface to form a protective film, thereby slowing down the speed and amount of iron atoms entering the zinc liquid, further reducing the generation of zinc slag, and its corrosion inhibition effect can also protect the substrate from corrosion, and also help the zinc liquid to better wet the surface of the substrate, improve the adhesion and uniformity of the coating, and combined with the addition of 1-carboxymethyl-3-methylimidazole tetrafluoroborate, it is found that it can improve the wettability of the zinc liquid to the substrate, making it easier for the zinc liquid to wet the surface of the substrate, significantly improving the adhesion and uniformity of the coating, and adding the above two additives to the plating solution significantly improves the adhesion and uniformity of the coating to the substrate.
[0027] Optionally, 0.5-1 wt % of sodium bisulfate is also added to the plating solution.
[0028] By adopting the above technical scheme, when sodium bisulfate is added to the plating solution as a zinc ammonium chloride salt film assistant, it helps to promote the formation of a protective film and make it more stable, and it helps to improve the surface tension and polarity of the plating solution, making it easier to react with steel and achieve a better wetting effect. In addition, during the subsequent hot-dip galvanizing, the protective film formed by the plating solution reacts with the zinc liquid to remove the protective film and form an iron-zinc alloy layer at the same time, and finally the adhesion and bonding between the substrate and the galvanized layer are better.
[0029] Optionally, in step 2), the hot-dip galvanizing temperature is 440-460°C.
[0030] In summary, this application has the following beneficial effects: 1. In the present application, the substrate is first subjected to water / abrasive sandblasting treatment, and then subjected to high-temperature heating, so that the iron oxide scale forms microcracks on the iron oxide scale under the above-mentioned mechanical action and thermal processing action, destroying the integrity of the iron oxide scale layer, and then subjected to reduction annealing treatment under reducing gas to provide a channel for the reducing gas to diffuse inward, accelerate the reduction process, especially the dense structure of the outer layer and the middle layer forms a channel, so that the iron oxide scale is reduced more thoroughly, so that the good adhesion between the galvanized layer and the substrate is improved through the reduction annealing treatment process in the present application, and the quality of hot-dip galvanizing is improved; 2. In the present application, the substrate treated with water / abrasive sandblasting is treated at high temperature, and the substrate is washed with water and then treated at high temperature. The substrate is treated under high temperature and water environment conditions, and then quickly treated in a sodium chloride salt solution, which is conducive to the cracking of the oxidized iron scale. Moreover, the substrate is quickly treated in a low temperature salt solution after high temperature treatment, and the integrity of the oxidized iron scale is destroyed by the change of thermal stress, which is more conducive to the circulation and reduction of the reducing gas in the subsequent reduction annealing process, and the reduction of the oxidized iron scale is more thorough. 3. In the present application, when the reduction annealing process is carried out, first, reduction is carried out in a hydrogen atmosphere to reduce ferric oxide and ferroferric oxide to iron or ferrous oxide, and then a small amount of carbon dioxide is used to provide an oxygen source, and carbon powder is sprayed onto the substrate at the same time, so that the carbon powder can exert its strong reducing property at high temperature and directly reduce the metal oxide. A small amount of carbon dioxide is introduced so that the participating carbon reacts with the carbon dioxide to generate carbon monoxide, so that the gas in the final reduction chamber is a mixed atmosphere of hydrogen and carbon monoxide. Compared with the traditional reduction annealing using only a reducing atmosphere, the reduction is usually not thorough. In the present application, a single carbon substance is introduced, and the regulation of the reducing gas is coordinated, so that the reduction of the iron oxide scale is more thorough, which is more conducive to the subsequent hot-dip galvanizing process. DETAILED DESCRIPTION
[0031] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0032] In the following examples, the hot-rolled steel strip substrate is a typical steel grade SPHC, with the chemical composition of 0.05wt% C, 0.02wt% Si, 0.20wt% Mn, 0.015wt% P, 0.015wt% S, 0.002wt% B and the balance of iron, and the initial thickness of the steel is 2.5 mm.
[0033] Example 1 A low carbon steel oxide scale reduction annealing process comprises the following steps: S1. Pretreatment: The hot-rolled steel strip substrate is first subjected to water / abrasive sandblasting treatment. The specific operation is as follows: water and quartz sand with a particle size of 40-80 mesh are mixed in a mass ratio of 1:0.15 to obtain a mortar, which is then sprayed onto the hot-rolled steel strip substrate. The spraying distance is 60 mm, the spraying pressure is 2 MPa, the spraying flow rate is 0.2 kg / min, the sandblasting angle is controlled to 50 degrees, and the sandblasting time is 4 min. After washing the substrate with water, the substrate is directly heated to 680°C at a heating rate of 55°C / s. After heat preservation treatment for 15 min, the substrate is taken out and immediately placed in a sodium chloride salt solution with a mass concentration of 40% at 5°C for cooling. After cooling to 340°C, the substrate is dried to obtain a pretreated substrate. S2, reduction annealing: the prepared pretreated substrate is first treated at 750° C. in a hydrogen atmosphere for 2 min, then 90% hydrogen and the remainder carbon dioxide are introduced, and carbon powder is sprayed onto the substrate at the same time, wherein the injection amount of the carbon powder is 0.1wt% of the hot-rolled steel substrate. After the treatment for 2 min, hydrogen is continued to be introduced, and the temperature is raised to 820° C. so that the gas pressure is reduced at 0.15 MPa for 3 min, and then the temperature is reduced to 520° C. at a cooling rate of 15° C. / s, and then cooled to 350° C. at a cooling rate of 35° C. / s, to complete the reduction annealing operation of the reduced iron sheet.
[0034] Example 2 A low carbon steel oxide scale reduction annealing process comprises the following steps: S1. Pretreatment: The hot-rolled steel strip substrate is first subjected to water / abrasive sandblasting treatment. The specific operation is as follows: water and quartz sand with a particle size of 40-80 mesh are mixed in a mass ratio of 1:0.1 to obtain a mortar, which is then sprayed onto the hot-rolled steel strip substrate. The spraying distance is 50 mm, the spraying pressure is 1.5 MPa, the spraying flow rate is 0.1 kg / min, the sandblasting angle is controlled to be 45 degrees, and the sandblasting time is 3 min. After washing the substrate with water, the substrate is directly heated to 650°C at a heating rate of 50°C / s. After heat preservation treatment for 10 min, the substrate is taken out and immediately placed in a sodium chloride salt solution with a mass concentration of 35% at 3°C for cooling. After cooling to 300°C, the substrate is dried to obtain a pretreated substrate. S2, reduction annealing: the prepared pretreated substrate is first treated at 700° C. in a hydrogen atmosphere for 2 min, then 85% hydrogen and the remainder carbon dioxide are introduced, and carbon powder is sprayed onto the substrate at the same time, and the injection amount of the carbon powder is 0.05wt% of the hot-rolled steel substrate. After treating for 2 min, hydrogen is continued to be introduced, and the temperature is raised to 780° C. so that the gas pressure is reduced at 0.1 MPa for 2 min, and then the temperature is cooled to 500° C. at a cooling rate of 10° C. / s, and then cooled to 300° C. at a cooling rate of 30° C. / s to complete the reduction annealing operation of the reduced iron sheet.
[0035] Example 3 A low carbon steel oxide scale reduction annealing process comprises the following steps: S1. Pretreatment: The hot-rolled steel strip substrate is first subjected to water / abrasive sandblasting treatment. The specific operation is as follows: water and quartz sand with a particle size of 40-80 mesh are mixed in a mass ratio of 1:0.2 to obtain a mortar, which is then sprayed onto the hot-rolled steel strip substrate. The spraying distance is 80 mm, the spraying pressure is 3.5 MPa, the spraying flow rate is 0.3 kg / min, the sandblasting angle is controlled to 60 degrees, and the sandblasting time is 5 min. After washing the substrate with water, the substrate is directly heated to 700°C at a heating rate of 60°C / s. After heat preservation treatment for 20 min, the substrate is taken out and immediately placed in a sodium chloride salt solution at 8°C and a mass concentration of 45% for cooling. After cooling to 380°C, the substrate is dried to obtain a pretreated substrate. S2, reduction annealing: the prepared pretreated substrate is first treated at 780° C. in a hydrogen atmosphere for 3 min, then 95% hydrogen and the remainder carbon dioxide are introduced, and carbon powder is sprayed onto the substrate at the same time, wherein the injection amount of the carbon powder is 0.15wt% of the hot-rolled steel substrate. After the treatment for 3 min, hydrogen is continued to be introduced, and the temperature is raised to 860° C. so that the gas pressure is reduced at 0.2 MPa for 3 min, and then the temperature is cooled to 560° C. at a cooling rate of 20° C. / s, and then cooled to 380° C. at a cooling rate of 40° C. / s, to complete the reduction annealing operation of the reduced iron sheet.
[0036] Example 4 A low carbon steel scale reduction annealing process is carried out according to the method in Example 1, except that the sandblasting angle in step S1 is 90 degrees.
[0037] Example 5 A low carbon steel scale reduction annealing process is carried out according to the method in Example 1, except that the sodium chloride salt solution in step S1 is at room temperature.
[0038] Example 6 A low carbon steel scale reduction annealing process is carried out according to the method in Example 1, except that in step S2, an equal amount of carbon dioxide is replaced by carbon monoxide, and no carbon powder is sprayed for treatment.
[0039] Example 7 A low carbon steel scale reduction annealing process is carried out according to the method in Example 1, except that in step S2, the steel is directly reduced in a hydrogen atmosphere at 800° C. for 7 minutes.
[0040] Comparative Example 1 A low carbon steel scale reduction annealing process is carried out according to the method in Example 7, except that step S1 is not performed.
[0041] Comparative Example 2 A low carbon steel scale reduction annealing process is carried out according to the method in Example 1, except that step S1 is not performed.
[0042] Comparative Example 3 A low carbon steel scale reduction annealing process is carried out according to the method in Example 1, except that the hot rolled strip steel substrate is first treated by water / abrasive sandblasting, then washed and dried to directly obtain a pretreated substrate for step S2, without heating, insulation and salt solution treatment.
[0043] Comparative Example 4 A low carbon steel scale reduction annealing process is carried out according to the method in Example 1, except that an equal amount of the sodium chloride solution in step S1 is replaced by water.
[0044] Comparative Example 5 A low carbon steel scale reduction annealing process is carried out according to the method in Example 1, except that the sodium chloride solution in step S1 is replaced by soybean oil in an equal amount.
[0045] Application Example 1 A low carbon steel hot dip galvanizing process comprises the following steps: 1) According to the method in Example 1, the hot rolled steel strip substrate is subjected to iron oxide reduction annealing treatment; 2) The substrate finally cooled to 350° C. in step S2 of Example 1 is first immersed in a plating solution and then dried, the immersion time is 15 s, the immersion temperature is 45° C., and the plating solution contains 6 wt % of ammonium chloride, 1.5 wt % of acidic amino acid-aspartic acid, 0.4 wt % of 1-carboxymethyl-3-methylimidazolium tetrafluoroborate, 12 wt % of zinc chloride and the balance of water; Then, it is placed in zinc liquid for hot-dip galvanizing. The hot-dip galvanizing temperature is 450°C. The hot-dip galvanizing is performed until the thickness of the galvanized layer is 30 microns. The zinc liquid includes 0.2wt% aluminum element, 0.06wt% magnesium element and the remainder zinc. A galvanized layer is formed on the surface of the hot-rolled strip to obtain a hot-dip galvanized sheet.
[0046] Application Example 2 A low carbon steel hot dip galvanizing process comprises the following steps: 1) performing scale reduction annealing treatment on the hot-rolled steel strip substrate according to the method in Example 2; 2) The substrate finally cooled to 300° C. in step S2 of Example 2 is first immersed in a plating solution and then dried, the immersion time is 10 s, the immersion temperature is 45° C., and the plating solution contains 5 wt % of ammonium chloride, 1 wt % of acidic amino acid-glutamic acid, 0.3 wt % of 1-carboxymethyl-3-methylimidazolium tetrafluoroborate, 10 wt % of zinc chloride and the balance of water; The hot-dip galvanizing is then carried out in a zinc liquid, the hot-dip galvanizing temperature is 440°C, the hot-dip galvanizing is carried out until the thickness of the galvanized layer is 30 microns, and the zinc liquid includes 0.15wt% of aluminum element, 0.05wt% of magnesium element and the remainder of zinc, a galvanized layer is formed on the surface of the hot-rolled strip, and a hot-dip galvanized sheet is obtained.
[0047] Application Example 3 A low carbon steel hot dip galvanizing process comprises the following steps: 1) According to the method in Example 3, the hot-rolled steel strip substrate is subjected to scale reduction annealing treatment; 2) The substrate finally cooled to 380° C. in step S2 of Example 3 is first immersed in a plating solution and then dried, the immersion time is 20 seconds, the immersion temperature is 50° C., and the plating solution contains 7wt% of ammonium chloride, 2wt% of acidic amino acid-glutamic acid, 0.5wt% of 1-carboxymethyl-3-methylimidazolium tetrafluoroborate, 15wt% of zinc chloride and the balance of water; Then, the steel strip is placed in a zinc liquid for hot-dip galvanizing at a temperature of 460°C until the thickness of the galvanized layer is 30 microns. The zinc liquid includes 0.3wt% of aluminum, 0.08wt% of magnesium and the remainder of zinc. A galvanized layer is formed on the surface of the hot-rolled steel strip to obtain a hot-dip galvanized sheet.
[0048] Application Example 4-7 A low carbon steel hot dip galvanizing process is carried out according to the method in Application Example 1, except that step 1) is carried out according to the iron oxide scale reduction annealing process in Examples 4-7 respectively.
[0049] Application Example 8 A low carbon steel hot dip galvanizing process is carried out according to the method in Application Example 1, except that 0.8 wt % of sodium bisulfate is also added to the plating solution in step 2).
[0050] Application Example 9 A low carbon steel hot dip galvanizing process is carried out according to the method in Application Example 1, except that 0.5 wt % of sodium bisulfate is also added to the plating solution in step 2).
[0051] Application Example 10 A low carbon steel hot dip galvanizing process is carried out according to the method in Application Example 1, except that 1 wt % of sodium bisulfate is also added to the plating solution in step 2).
[0052] Application Example 11 A low carbon steel hot dip galvanizing process is carried out according to the method in Application Example 8, except that an equal amount of sodium bisulfate is replaced by sodium bisulfite.
[0053] Application Example 12 A low carbon steel hot dip galvanizing process is carried out according to the method in Application Example 1, except that acidic amino acid and 1-carboxymethyl-3-methylimidazole tetrafluoroborate are not added to the plating solution.
[0054] Application Example 13 A low carbon steel hot dip galvanizing process is carried out according to the method in Application Example 1, except that no acidic amino acid is added to the plating solution.
[0055] Application Example 14 A low carbon steel hot dip galvanizing process is carried out according to the method in Application Example 1, except that 1-carboxymethyl-3-methylimidazole tetrafluoroborate is not added to the plating solution.
[0056] Comparative Application Examples 1-5 A low carbon steel hot dip galvanizing process is carried out according to the method in Application Example 1, except that step 1) is carried out according to the methods in Comparative Examples 1-5 respectively.
[0057] Performance Testing First, the galvanized sheets obtained in the application examples and comparative application examples were subjected to cold bending tests using a universal testing machine to observe the integrity and cracking of the coating. It can be seen that the coating of the galvanized sheets obtained in the application examples of the present application can maintain good integrity after cold bending, and there are no obvious cracks visible to the naked eye on the bent surface, indicating that the galvanized layer has good ductility. At the same time, the adhesion of the galvanized layer to the substrate is good and can meet industrial needs, indirectly indicating that the iron oxide scale is more thoroughly removed during the reduction process, thereby improving the adhesion of the coating; while in comparative application example 1, after the cold bending test of the galvanized sheet, obvious cracking and shedding occurred in the galvanized layer, and the adhesion of the galvanized layer to the substrate was poor. In comparative application example 2, after the cold bending test of the galvanized sheet, slight cracking and shedding occurred in the galvanized layer.
[0058] In order to more clearly consider the reduction effect in the iron oxide reduction process and the adhesion performance between the coating and the substrate, the galvanized steel sheets obtained in the corresponding use cases and comparative application examples of the reference standard GB / T 9286-1998 "Scratch test for paint and varnish films" were used to measure the coating scratch resistance and rate it. The rating standards are shown in Table 1 below.
[0059] Table 1: The test results are shown in Table 2 below. In addition, the galvanized steel prepared in the application example of this application and the comparative application example was subjected to a neutral salt spray test in accordance with GB / T10125 standard to measure the time for red rust to appear on the surface of the sample. The test results are shown in Table 2 below.
[0060] Table 2: Combined with the test results of Table 1 and Table 2 above, the application examples 1-3 of the present application adopt the iron oxide reduction annealing process and the specific plating solution treatment in the present application and then hot dip galvanizing to obtain excellent adhesion between the galvanized sheet and the substrate, and the final coating quality is better, with more excellent corrosion resistance, and the surface of the obtained galvanized layer is smooth and uniform, without obvious roughness, bubbles, scratches, cracks and other defects. Combined with the test results of application examples 1 and 4, it can be seen that the sandblasting angle in the iron oxide reduction annealing process will affect the destruction effect of the iron oxide, thereby affecting the subsequent reduction The effect, which in turn affects the final adhesion performance and coating quality. Combined with the test results of Application Example 5, placing the substrate directly in a low-temperature salt solution after high temperature is more conducive to destroying the integrity of the iron oxide scale, promoting the reduction process, and improving the final coating quality and adhesion. Referring to the test results of Application Examples 6 and 7, in Application Example 6, no carbon powder and carbon dioxide conditions were applied during the annealing reduction process, but carbon monoxide conditions were directly introduced, and its reduction effect was significantly reduced, and the adhesion and coating quality were significantly reduced. When the traditional hydrogen atmosphere was used for reduction in Application Example 7, its performance was further reduced.
[0061] Combined with the test results of Application Example 1 and Comparative Application Examples 1 and 2, it can be seen that when the substrate is not pretreated in step S1 and the traditional hydrogen reduction scheme is adopted, its adhesion and coating quality are significantly reduced, and even in Comparative Application Example 2, even if the atmosphere adjustment reduction system of carbon powder + carbon dioxide and hydrogen and carbon monoxide is adopted, but when it is not subjected to the iron oxide skin layer destruction treatment in step S1, its reduction degree is low, and its coating quality and adhesion performance of the coating are significantly reduced; combined with the test results of Comparative Application Example 3, when the substrate is pretreated, when it is only sandblasted without subsequent heating and salt solution cooling treatment, its adhesion is also significantly reduced, and combined with Comparative Application Examples 4 and Comparative Application Examples 5, when the cooling solvent is replaced with commonly used water or oil solvents, its effect is also reduced compared to the salt solution in Application Example 1.
[0062] In addition, referring to the test results of Application Examples 1 and 8-10, it can be seen that when sodium bisulfate is added to the plating solution, the wetting performance of the zinc solution on the substrate is improved, and the coating quality is further improved. Combined with the test results of Application Example 12, when the plating solution uses a traditional ammonium chloride and zinc chloride composite salt solution, compared with Application Example 1, the coating quality is reduced and the corrosion resistance is reduced. When sodium bisulfite is used in Application Example 11, the coating quality is reduced compared with sodium bisulfate. Combined with the test results of Application Examples 13 and 14, when only acidic amino acids or 1-carboxymethyl-3-methylimidazole tetrafluoroborate are added to the plating solution, the coating quality is significantly reduced.
[0063] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A process for reducing and annealing low carbon steel oxide scale, characterized in that: The following steps are involved: S1. Pretreatment: The hot-rolled steel strip substrate is first treated by water / abrasive sandblasting and then washed with water, and then heated to 650-700°C at a heating rate of 50-60°C / s. After the heat preservation treatment, the substrate is taken out and immediately placed in a salt solution to obtain a pretreated substrate; S2. Reduction annealing: The prepared pretreated substrate is subjected to reduction annealing in a reducing gas atmosphere at a reduction temperature of 700-860°C.
2. A low carbon steel oxide scale reduction annealing process according to claim 1, characterized in that: In step S1, the specific operation of water / abrasive sandblasting is: Water and quartz sand are mixed in a mass ratio of 1: (0.1-0.2) to obtain mortar, which is then sprayed onto the hot-rolled strip steel substrate at a spray distance of 50-80 mm, a spray pressure of 1.5-3.5 MPa, and a spray flow rate of 0.1-0.3 kg / min.
3. A low carbon steel oxide scale reduction annealing process according to claim 2, characterized in that: The particle size of the quartz sand is 40-80 mesh, the sandblasting angle is controlled to be 45-60 degrees, and the sandblasting time is 3-5 minutes.
4. A low carbon steel oxide scale reduction annealing process according to claim 1, characterized in that: The salt solution in step S1 is a sodium chloride salt solution with a mass concentration of 35-45%, and its temperature is controlled at 3-8°C.
5. A low carbon steel oxide scale reduction annealing process according to claim 1, characterized in that: In step S2, the substrate is first treated in a hydrogen atmosphere at 700-780°C for 2-3 minutes, and then 85-95% hydrogen and the remainder of carbon dioxide are introduced, and carbon powder is sprayed onto the substrate at the same time. After treating for 2-3 minutes, hydrogen is continued to be introduced, and the temperature is raised to 780-860°C so that the gas pressure is reduced to 0.1-0.2MPa.
6. A low carbon steel oxide scale reduction annealing process according to claim 5, characterized in that: The amount of carbon powder added in step S2 is 0.05-0.15wt% of the hot-rolled steel substrate.
7. A low carbon steel oxide scale reduction annealing process according to claim 1, characterized in that: In step S2, the pretreated substrate is reduced in a reducing gas atmosphere, cooled to 500-560°C at a cooling rate of 10-20°C / s, and then cooled to 300-380°C at a cooling rate of 30-40°C / s.
8. A low carbon steel hot dip galvanizing process, characterized in that: The following steps are involved: 1) Performing an iron scale reduction annealing treatment on a hot-rolled steel strip substrate according to the low-carbon steel iron scale reduction annealing process as claimed in any one of claims 1 to 7; 2) The hot-rolled steel strip after the reduction annealing treatment of the iron oxide scale is hot-dip galvanized in zinc liquid to form a galvanized layer on the surface of the hot-rolled steel strip to obtain a hot-dip galvanized sheet.
9. A low carbon steel hot dip galvanizing process according to claim 8, characterized in that: In step 2), the zinc solution includes 0.15-0.3wt% of aluminum, 0.05-0.08wt% of magnesium and the balance of zinc.
10. A low carbon steel hot dip galvanizing process according to claim 8, characterized in that: Step 2) The hot dip galvanizing temperature is 440-460℃.
Citation Information
Cited By
Method and system for controlling high zinc content of hot-dip galvanized steel pipe
CN121161201A
420MPa-grade galvanized low-alloy high-strength steel and production method thereof
CN121951392A
420mpa grade galvanized low alloy high strength steel and method of production thereof
CN121951392B